Embedding electronic patient-reported outcome measures into routine care for patients with stage III MELanoma (ePROMs-MEL): protocol for a prospective, longitudinal, mixed-methods pilot study. Issue 12 (20th December 2022) - Dempsey, Kathy; Saw, Robyn; Bartula, Iris; Lo, Serigne; Lawn, Craig; Pennington, Thomas; Spillane, Andrew; Boyle, Frances; Dong, Skye; Dieng, Mbathio; Milne, Donna; Seaman, Linda; et al.
Abstract : Introduction: The benefits of patient-reported feedback, using questionnaires that allow patients to report how they feel and function without any interpretation from healthcare professionals, are well established. However, patient-reported outcomes measures (PROMs) are not routinely collected in patients with melanoma in Australia. The aim of this study is to evaluate the feasibility and acceptability of implementing electronic PROMs (ePROMs) into routine care from the perspectives of patients with stage III melanoma and their treating clinical team. Methods and analysis: A minimum of 50 patients and 5 clinicians will be recruited to this prospective, longitudinal pilot study (ePROMs-MELanoma). The study uses a mixed-methods approach (quantitative PROMs questionnaires and end-of-study surveys with qualitative interviews) and commenced in May 2021 in surgical and medical melanoma clinics at two sites in metropolitan Sydney, Australia. The primary outcomes are measures of feasibility and acceptability, comprising descriptive questionnaire completion statistics, and proportion of patients who reported that these PROMs were easy to complete and measured items they considered important. Clinician and clinic staff views will be canvassed on the appropriateness of these PROMs for their patients, change in referral practice and uptake and incorporation into routine practice. Secondary aims include measurement of improvements in patients' emotional and physical health and well-being, and utility of real-time data capture and clinician feedback. All participants will complete the Distress Thermometer and EQ-5D-5L questionnaires in the clinic using a tablet computer at baseline and two to three subsequent follow-up appointments. Participants who report a score of 4 or higher on the Distress Thermometer will be triaged to complete an additional three questionnaires: the QLQ-C30, Depression, Anxiety and Stress Scale and Melanoma Concerns Questionnaire-28. Results will be generated in real time; patients with psychosocial distress or poor quality of life will discuss possible referral to appropriate allied health services with their clinician. Thematic analysis of interviews will be conducted. Ethics and dissemination: Ethics approval obtained from St Vincent's Hospital Human Research Ethics Committee on 19 September 2019 (2019/ETH10558), with amendments approved on 8 June 2022. Patient consent is obtained electronically prior to questionnaire commencement. Dissemination strategies will include publication in peer-reviewed journals and presentation at international conferences, tailored presentations for clinical societies and government bodies, organisational reporting through multidisciplinary meetings and research symposia for local clinicians and clinic staff, and more informal, lay reports and presentations for consumer melanoma representative bodies and patient participants and their families. Trial registration number: ACTRN12620001149954.